Synthesis and Charaterization of Lanthanide Complexes of Schiff Bases Derived from 2,6-Diacetyl Pyridine Monoxime and Diamino Benzene - Kumar, R.N.; Kumari Chauhan, Nilam; Kumar Singh, Sudhir (Asian Journal of Chemistry, 2010)
The La, Pr, Nd, Sm, Eu and Gd complexes of bis-(2,6-diacetyl pyridine monoxime) 1,2-diamino benzene (L1) and bis-(2,6-diacetyl pyridine monoxime) 1,3-diamino benzene (L2) with chloride as counter ions have been synthesised through the metal template effect. They are formulated as [Ln(DAPMB)2CI2]Cl (DAPMB = Schiff bases) on the basis of UV-VIS, IR 1H NMR spectroscpic data, magnetic susceptibility measurement and elemental anlaysis.